The cytochrome P450 CYP72A552 is key to production of hederagenin‐based saponins that mediate plant defense against herbivores. Issue 3 (25th February 2019) - Liu, Qing; Khakimov, Bekzod; Cárdenas, Pablo D.; Cozzi, Federico; Olsen, Carl Erik; Jensen, Karen Rysbjerg; Hauser, Thure Pavlo; Bak, Søren
Summary: Plants continuously evolve new defense compounds. One class of such compounds is triterpenoid saponins. A few species in the Barbarea genus produce saponins as the only ones in the large crucifer family. However, the molecular mechanism behind saponin biosynthesis and their role in plant defense remains unclear. We used pathway reconstitution in planta, enzymatic production of saponins in vitro, insect feeding assays, and bioinformatics to identify a missing gene involved in saponin biosynthesis and saponin‐based herbivore defense. A tandem repeat of eight CYP72A cytochromes P450 colocalise with a quantitative trait locus (QTL) for saponin accumulation and flea beetle resistance in Barbarea vulgaris . We found that CYP72A552 oxidises oleanolic acid at position C‐23 to hederagenin. In vitro ‐produced hederagenin monoglucosides reduced larval feeding by up to 90% and caused 75% larval mortality of the major crucifer pest diamondback moth and the tobacco hornworm. Sequence analysis indicated that CYP72A552 evolved through gene duplication and has been under strong selection pressure. In conclusion, CYP72A552 has evolved to catalyse the formation of hederagenin‐based saponins that mediate plant defense against herbivores. Our study highlights the evolution of chemical novelties by gene duplication and selection for enzyme innovations, and the importance of chemical modification in plant defense evolution.